Mirroring as an a priori symmetry - Saunders, S (University of Chicago Press, 2007)
A relationist will account for the use of 'left' and 'right' in terms of relative orientations, and other properties and relations invariant under mirroring. This analysis will apply whenever mirroring is a symmetry, so it certainly applies to classical mechanics; we argue it applies to any physical theory formulated on a manifold: it is in this sense an a priori symmetry. It should apply in particular to parity violating theories in quantum mechanics; mirror symmetry is only broken in such theories as a special symmetry.